2021
DOI: 10.1128/jvi.00597-21
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and Local Specificity of the Virome Associated with Tospovirus-Transmitting Thrips Species

Abstract: Frankliniella occidentalis (western flower thrips=WFT) and Thrips tabaci (onion thrips=OT) are insect species that greatly impact horticultural crops through direct damage and their efficient vectoring of tomato spotted wilt virus and iris yellow spot virus. In this study we collected thrips of these species from 12 field populations in various regions in Italy. We also included one field population of Neohydatothrips variabilis (soybean thrips=ST) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 78 publications
(109 reference statements)
2
33
0
Order By: Relevance
“…The 3,960 nt long sequence of RNA2 includes Sanger confirmed 5 UTR and CDS and one complete ORF encoding a predicted protein of 1,228 aa (predicted M r = 134.058 kDa). Based on BlastX, the insect narna-like virus 1 (Chiapello et al, 2021) hosted by thrips (insect pest Frankliniella occidentalis) showed highest similarity with RNA2 of HetNlV1 (Table 1). Phylogenetic analysis showed placement of HetNlV1 in a highly supported cluster including viruses from Plasmopara viticola lesions and thrips (Chiapello et al, 2020(Chiapello et al, , 2021; Figure 2B).…”
Section: A Novel Bisegmented Narna-like Virus Hosted By Heterobasidionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3,960 nt long sequence of RNA2 includes Sanger confirmed 5 UTR and CDS and one complete ORF encoding a predicted protein of 1,228 aa (predicted M r = 134.058 kDa). Based on BlastX, the insect narna-like virus 1 (Chiapello et al, 2021) hosted by thrips (insect pest Frankliniella occidentalis) showed highest similarity with RNA2 of HetNlV1 (Table 1). Phylogenetic analysis showed placement of HetNlV1 in a highly supported cluster including viruses from Plasmopara viticola lesions and thrips (Chiapello et al, 2020(Chiapello et al, , 2021; Figure 2B).…”
Section: A Novel Bisegmented Narna-like Virus Hosted By Heterobasidionmentioning
confidence: 99%
“…High-throughput sequencing (HTS) studies have recently revolutionized our understanding on the virosphere and revealed numerous novel virus clades that await classification by the International Committee on Taxonomy of Viruses (ICTV). Among these are many new fungal narna-like viruses ( Chiapello et al, 2020 , 2021 ; Sutela et al, 2020 ; Chiba et al, 2021 ; Jia et al, 2021 ) and the unclassified virus group tentatively named “ambiviruses” recently detected in asco- and basidiomycetous fungi ( Sutela et al, 2020 ; Forgia et al, 2021 ; Linnakoski et al, 2021 ). The accumulating sequence information has also led to the recognition of new host taxa for viruses, for example, plants as hosts for mitoviruses ( Nibert et al, 2018 ) and fungi as hosts of ourmia-like viruses (now classified in the viral family Botourmiaviridae in order Ourlivirales ), and the re-classification of many fungal viruses, for example, the division of family Narnaviridae into Mitoviridae and Narnaviridae .…”
Section: Introductionmentioning
confidence: 99%
“…During the fruit-ripening period, the fruit has red-yellow or red-white ring spots and bright yellow ring markings, particularly the The rapid spread of Frankliniella occidentalis (Western flower thrips) carrying the TSWV has seriously harmed tomato cultivation and production. The TSWV reduces yield in large areas and the marketable value of tomato or even causes the death of tomato plants [25,26]. Numerous tomato plants (such as those that carry the Sw-5 gene) resistant to the TSWV have been screened, and many excellent reviews on the different aspects of TSWV biology, thrips vector-mediated transmission, resistance strategies, and plants' innate immunity to the TSWV have been published [10,[27][28][29][30][31][32][33].…”
Section: Tswv Symptoms In Tomato Plantsmentioning
confidence: 99%
“…Susceptible plants were inoculated with TSWV isolates at the four-, five, and six-leaf stages and cultivated for symptom development. Then, systemically infected plants were fed to the first instar larvae (0-2 h old) of Frankliniella occidentalis for 2 days to carry the TSWV isolates [26]. The viruliferous larvae were cultivated into adults on healthy plants.…”
Section: Thrip Inoculationmentioning
confidence: 99%
“…Following the emerging trend in virology, recently described nidoviruses have been discovered by bioinformatics analysis of next or third generation sequencing data from meta-genomic andtranscriptomics studies of diverse specimens [6,7,[21][22][23][24][25][26][27][28][29][30][31][32][33][34]. These data sets are composed of overlapping sequence fragments of variable lengths (so-called reads) of various origins that can be assembled into contigs, some of which may represent full-length or partial viral genomes.…”
Section: Introductionmentioning
confidence: 99%